Effect of Zinc and Silica Solubilizing Bacterial Consortia on Yield and Soil Enzyme Activity of Direct Sown Rice - Babu, S. V.; Gopal, A. V.; Trimurtulu, N.; Babu, G. K.; Bhattiprolu, S. L. (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during late kharif (November, 2019) and late rabi (April, 2020) seasons, 2019 with 13 treatments, replicated thrice, at Agricultural Research Station, Jangamaheswarapuram, Andhra Pradesh, India to evaluate the effect of zinc and silica solubilizing bacterial consortia on yield and yield attributes of rice, zinc and silica content in plant and grain, soil enzyme activity. Among the treatments viz., T1: RDF (Control); T2: RDF+ZnSO4 at 25 kg ha-1; T3: RDF + Calcium silicate at 120-200 kg ha-1, T4: RDF+ZnSO4 at 25 kg ha-1+ Calcium silicate at 120-200 kg ha-1; T5: RDF+ZnKJJ-4; T6: RDF+ZnPGG-1; T7: RDF+SiKPP-1; T8: RDF+SiPYY-3; T9: RDF+ZnKJJ-4 and ZnPGG-1; T10: RDF+SiKPP-1 and SiPYY-3; T11: RDF+ZnKJJ-4+SiKPP-1; T12: RDF+ZnPGG-1+SiPYY-3 and T13: RDF+ZnKJJ-4 and ZnPGG-1+SiKPP-1 and SiPYY-3, highest zinc (0.79 and 0.81ppm) and silica content (0.89 and 0.99ppm) in plant was recorded with RDF + ZnKJJ-4 and ZnPGG-1+SiKPP-1 and SiPYY-3 at 45 days after sowing (DAS) and 120 DAS, respectively. At 120 DAS, highest zinc (0.58 ppm) and silica content (0.98ppm) in grain; highest dehydrogenase enzyme activity (390.4 and 499.6 µg TPF g-1 day-1), acid phosphatase activity (58.15 and 68.35 µg pNP g-1 h-1), alkaline phosphatase activity (130.52 and 136.81 µg pNP g-1 h-1) and urease enzyme activity (40.04 and 50.06 µg of NH4 + -N g-1 soil 2h-1) at 45 DAS and 120 DAS; highest plant height at 45 DAS and 90 DAS (38.4 and 96.6 cm), total no. of tillers (496 m2), highest panicle length at harvest (18.2 cm), no. of grains panicle-1 (157), no. of filled grains panicle-1 (140), 1000 grain weight (19.2 g), grain yield (5523 kg ha-1) and straw yield (6893 kg ha-1) were recorded with this treatment..Hence application of zinc and silica solubilizing bacterial consortia was better in improving enzyme activities in soil, releasing essential plant nutrients and thus quantity and quality of Rice yields.